Z działalności najstarszej placówki poradnictwa psychologiczno-pedagogicznego w Poznaniu - Knocińska, Anna (Biuletyn Historii Wychowania, 2014)
The oldest institution of psychological and pedagogical counselling in Poznań has been operating for almost sixty years. We are referring to the Psychological and Pedagogical Clinic for Children and Young People with Special Educational Needs, currently located on Ulica 28 Czerwca, 1956, no. 296/298. It’s origins date back to 1957, when the efforts of the school authorities and academic circles in Poznań created the Psychological Clinic in Poznań. Since it started operating to the present day almost everything has changed. The institution has been subject over the years to numerous reforms, be they administrative, educational, or to the system of providing psychological and educational assistance. The name of the institution has changed four times, the range of tasks has been repeatedly redefined, continually expanding, and the supervising authorities and area of operation have changed. Undeniably, though, it has always played an extremely important role for the children and young people under its care, providing vital real life.